Managing quality for job performance: is paternalistic leadership behavior an alternative to influence trust? / Ahmad Fikri Mohd Kassim ... [et al.] - Mohd Kassim, Ahmad Fikri; Razali, Norizatul Mazni; Mohd Rosli, Norfaezah; Mohd Aznan, Ellail ain; Khor, Poy Hua (Universiti Teknologi MARA, Perlis, 2021)
Successful leaders play a complex role. Leaders may manipulate followers to accomplish goals since they have authority and power to influence. Interestingly, Paternalistic leadership has qualities of attributes not only on the reactions of dyadic systems and followers but also subordinates’ attitude and behaviour. Paternalistic leadership flows from a particular cultural context. A family environment is created by paternalistic leaders in the management system. They display 'goodwill' and act as a leader in family approaches towards staff. Currently, there is no specifically conducted gender-based research at the university level specifically to analyze the perceptions of paternalistic leadership on job performance and trust among the staff of the university. Therefore, this study focused primarily on the perceptions of paternalistic leadership behaviour among staff members at the university level. A total of 254 respondents from UiTM Perlis staffs (male, n = 125; female n = 129) from four departments [Student Affairs, academic affairs, administration, and academic staff (lecturers)] completed a questionnaire pack assessing the study variables. Results revealed that (i) there are significant correlations in the dimension of paternalistic leadership, job performance, and trust perceived by staff at UiTM Perlis Branch, (ii) there are no significant differences in the dimension of paternalistic leadership, job performance, and trust between gender by staff at UiTM Perlis Branch. In conclusion, a leader who can create a better work environment can enhance staff competencies and influence trust in them.